Planar chiral AIEgens based on [2.2]paracyclophane as efficient solid-state deep red circularly polarized luminescent emitters. (January 2023) - Ji, Honghan; Liu, Wenjing; Huo, Yanmin; Han, Miao; Yao, Qingxia; Gong, Shuwen; Duan, Wenzeng
Abstract: In this work, a series of [2.2]paracyclophane-based 4-(dicyanomethylene) -4 H -pyran compounds (2a −2d ) with aggregation-induced emission (AIE) and circularly polarized luminescence (CPL) properties were designed and synthesized. These compounds exhibit orange and deep red emissive fluorescence at 585–686 nm with high fluorescence quantum yields ( Φ f ) of 40–97% in solid-state. More importantly, ( R p )/( S p )-2a −2b form different aggregation states due to the influence of different substituents, resulting in different Cotton effects. Moreover, ( R p )/( S p )-2a −2b display aggregation-induced circularly polarized luminescence (AICPL) signals in the deep red region with moderate luminescence dissymmetry factors (1.4–1.9 × 10 −3 ). These photophysical properties are rationalized by single crystal structure analysis, TD-DFT calculations, cyclic voltammetry and SEM. These results clearly demonstrate the introduction of strong electron-accepting group on [2.2]paracyclophane derivatives to enhance the ICT process is an efficient approach to construct planar chiral deep red circularly polarized luminescence emitters. Graphical abstract: Image 1 Highlights: Planar chiral AIEgens based on [2.2]paracyclophane were designed and synthesized. ( R p )/( S p )-2a −2b show distinct CD signals and AICPL properties with .| g lum | up to 1.9 × 10 −3 . 2a −2d exhibit orange to deep red emission (585–686 nm) with high solid-state Φ f (40–97%).